Diffractive dijet production with a leading proton in ep collisions at HERA - Andreev, Vladimir; Herbst, Michael Clemens; Huber, Florian; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (Journal of high energy physics, 2015)
The cross section of the diffractive process e+p → e+Xp is measured at a centre-of-mass energy of 318 GeV, where the system X contains at least two jets and the leading final state proton p is detected in the H1 Very Forward Proton Spectrometer. The measurement is performed in photoproduction with photon virtualities Q2< 2 GeV2 and in deep-inelastic scattering with 4 GeV2< Q2< 80 GeV2. The results are compared to next- to-leading order QCD calculations based on diffractive parton distribution functions as extracted from measurements of inclusive cross sections in diffractive deep-inelastic scattering.
Gesehen am 23.07.2020